Association between menthol-flavoured cigarette smoking and flavoured little cigar and cigarillo use among African-American, Hispanic, and white young and middle-aged adult smokers. (7th October 2016) - Sterling, K; Fryer, C; Pagano, I; Jones, D; Fagan, P
Abstract : Objectives: Flavour additives in cigarettes and little cigars and cigarillos (LCCs), which influence smokers' risk perceptions, may reinforce dual flavoured tobacco use. We examined the association among mentholated cigarette use, risk perceptions for flavour additives in LCCs and flavoured LCC smoking behaviour. Methods: Data from a national probability sample of 964 young and middle-aged adult current cigarette smokers were analysed. Multinomial logistic regression models examined the relationship among mentholated cigarette smoking, risk perceptions and current flavoured LCC use for the analytic sample and gender and race/ethnicity. Results: Daily menthol cigarette smokers, compared to occasional, non-menthol smokers, had increased odds of flavoured LCC smoking (OR=1.75, 95% CI 1.02 to 2.98). This relationship was found for males, blacks/African-Americans and Hispanics/Latinos (p<0.05). Positive perceptions of menthol-flavoured additives in LCCs was associated with increased odds of flavoured LCC use among the analytic sample, males and blacks/African-Americans (p<0.05). Positive perceptions for clove-flavoured, spice-flavoured and alcohol-flavoured additives were also associated with flavoured LCC use among the analytic sample (p<0.05). Conclusions: Use of menthol-flavoured cigarettes and positive perceptions about menthol-flavoured and other flavour additives in LCCs may contribute to dual use with flavoured LCCs among adult cigarette smokers, specifically those from vulnerable populations.